Combined Auxiliary Networks and Bird's Eye View Method for Real-Time Multicategory Object Recognition. (9th March 2021) - Gong, Zhangpeng; Wei, Luansu; Wang, Guoye; Xu, Dongxin; Ge, Chang
Abstract : Object recognition based on LIDAR data is crucial in automotive driving and is the subject of extensive research. However, the lack of accuracy and stability in complex environments obstructs the practical application of real-time recognition algorithms. In this study, we proposed a new real-time network for multicategory object recognition. The manually extracted bird's eye view (BEV) features were adopted to replace the resource-consuming 3D convolutional operation. Besides the subject network, we designed two auxiliary networks to help the network learn the pointwise features and boxwise features, aiming to improve the category and bounding boxes' accuracy. The KITTI dataset was adopted to train and validate the proposed network. Experimental results showed that, for hard mode, the total average precision (AP) of the category reached 97.4%. For an intersection over a union threshold of 0.5 and 0.7, the total AP of regression reached 93.2% and 85.5%; especially, the AP of car's regression reached 95.7% and 92.2%. The proposed network also showed consistent performance in the Apollo dataset with a processing duration of 37 ms. The proposed network exhibits stable and robust object recognition performance in complex environments (multiobject, unordered objects, and multicategory). And it shows sensitivity to occlusion of the LIDAR system and insensitivity to close large objects. The proposed multifunction method simultaneously achieves real-time operation, high accuracy, and stable performance, indicating its great potential value in practical application.